Enhancing the CO2 Adsorption Performance of UiO-66 by Imidazolium-Based Room-Temperature Ionic Liquids (RTILs) Incorporation - Laela Mukaromah; Andi Haryanto; Yessi Permana; Aep Patah (Universitas Gadjah Mada, 2023)
Functionalization of metal-organic frameworks resulting in efficient CO2 adsorption materials became substantial in preventing the worsening environment upon the emission of CO2. In this study, several room-temperature ionic liquids (RTILs) with an imidazolium-based cation of 1-butyl-3-methylimidazolium [bmim]+ and anions of bis(trifluoromethylsulfonyl)imide [TFSI]−, trifluoromethanesulfonate [OTf]−, hexafluorophosphate [PF6]−, and tetrafluoroborate [BF4]− were incorporated into UiO-66 by wet impregnation method under air. The RTILs/UiO-66 composites were characterized by PXRD, FTIR, TGA, nitrogen physisorption, and CO2 adsorption. Based on the type of anions of imidazolium-based RTILs, the CO2 uptake of RTILs/UiO-66 composites followed the trend: [OTf]− > [TFSI]− > [PF₆]− > [BF₄]− at low temperature (273 K) and pressure (100 kPa). The CO2 uptake of pristine UiO-66 increased approximately 1.5 times upon incorporating [bmim][OTf]. The type of anions of imidazolium-based RTILs influences the CO2 adsorption performance of RTILs/UiO-66 composites in which anions containing fluoroalkyl group ([OTf]−, [TFSI]−) exhibited a higher CO2 uptake compared to inorganic fluorinated anions ([BF4]−, [PF6]−). Hence, the incorporation of hydrophobic imidazolium-based RTILs showed a potential to enhance the performance of UiO-66 for CO2 adsorption application.